English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

(2pq²)(-3p²q)²

2006-11-26 07:20:48 · 1 answers · asked by Anonymous in Science & Mathematics Mathematics

1 answers

Expand: (2pq²) (-3p²q) (-3p²q)

Multiply all co-efficients. (2) (-3) (-3) = 18

Add exponents of 'p' [1 + 2 + 2] = 5

Add exponents of 'q' [2 + 1 + 1] = 4

Ans = 18 p^5 q^4 (^5 and ^4 denote exponents)

2006-11-26 12:46:03 · answer #1 · answered by SPLATT 7 · 1 0

fedest.com, questions and answers